The world reimagined : Americans and human rights in the twentieth century - Bradley, Mark, 1961- (2016)
"For readers who want to understand why human rights has become the moral language of our time. It explores the making of a twentieth century global human rights imagination and its American vernaculars in times of war, decolonization and globalization during the transformative decades of the 1940s and 1970s"--Provided by publisher.
Introduction : how it feels to be free -- Part One. The 1940s. At home in the world -- The wartime rights imagination -- Beyond belief -- Conditions of possibility -- Part Two. The 1970s. Circulations -- American vernaculars I -- American vernaculars II -- The movement -- Coda : the sense of an ending.
Includes bibliographical references (pages 241-294) and index.
Keywords: Human rights -- United States -- History -- 20th century; Human rights -- Language -- History -- 20th century; Social change -- History -- 20th century; War -- Moral and ethical aspects -- History -- 20th century; Decolonization -- History -- 20th century; Globalization -- Political aspects -- History -- 20th century; Transnationalism -- Political aspects -- History -- 20th century; World politics -- 1945-1989.; Menschenrecht; Politische Sprache; Politische Kultur; United States -- Foreign relations -- 1945-1989.; USA